Transpacific Femininities : The Making of the Modern Filipina - Cruz, Denise, 1975- (Book collections on Project MUSE., 2012)
Focusing on the early to mid-twentieth century, Denise Cruz illuminates the role that a growing English-language Philippine print culture played in the emergence of new classes of transpacific women.